1984
DOI: 10.1159/000241883
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Catecholamine Responses to Successive Episodes of Hypoxemia in the Fetus

Abstract: The cardiovascular and plasma catecholamine responses to successive episodes of hypoxemia were evaluated in 5 fetal lambs in utero (≥ 0.7 gestation). Fetal heart rate (HR) and blood pressure (BP) were monitored continuously and specimens obtained for arterial blood gases, plasma norepinephrine (NE) and epineprine (E) during a baseline control period, during each of 5 hypoxemic episodes and during 4 intervening recovery periods. Hypoxemia (PO2 = 9.8–13.7 Torr) was produced by gradual, controlled cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…This effect is consistent with other studies in which fetal hypoxia was produced by a reduction in uterine blood flow [5,6,9] or secondarily by maternally inspired, low-oxygen gas mixtures [13,14]. The rebound tachycardia has been reported previously [5,15] and is postulated to occur as a result of the increased circulating cate cholamines released by the fetus in response to hypoxic stress [6,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…This effect is consistent with other studies in which fetal hypoxia was produced by a reduction in uterine blood flow [5,6,9] or secondarily by maternally inspired, low-oxygen gas mixtures [13,14]. The rebound tachycardia has been reported previously [5,15] and is postulated to occur as a result of the increased circulating cate cholamines released by the fetus in response to hypoxic stress [6,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…As reported by others for partial cord occlusions (Giussani et al, 1997), we observed that following the initial bradycardia fetal heart rate stabilized or even increased slightly only to fall again during the last minute of occlusion. This transient increase in heart rate parallels the increase in arterial pressure and thus may also be the result of increased sympathetic drive (Lewis et al, 1984). In contrast to the bradycardia of the first minute, fetal heart rate in pre-existing hypoxia fetuses was significantly lower than in normoxic fetuses during the last minute only in the last three occlusions.…”
Section: Discussionmentioning
confidence: 85%
“…Acute hypoxemia increases plasma concentrations of norepinephrine, epinephrine, and vasopressin (20), and also increases plasma glucagon concentrations (2 1) in fetal lambs. Acute cord compression similarly increases norepinephrine and epinephrine (22); however, changes in glucagon, vasopressin, and angiotensin I1 have not been studied. Determination of the specific role of each of these hormones as stimuli for fetal hepatic glucose release during hypoxemia or cord compression will require further study using specific antagonists.…”
Section: Discussionmentioning
confidence: 98%